Erodibility of low‐compaction steep‐sloped reclaimed surface mine lands in the southern Appalachian region, USA. Issue 3 (6th February 2014) - Hoomehr, Siavash; Schwartz, John S.; Yoder, Daniel; Drumm, Eric C.; Wright, Wesley
Abstract The use of loose spoils on steep slopes for surface coal mining reclamation sites has been promoted by the US Department of Interior, Office of Surface Mining for the establishment of native forest, as prescribed by the Forest Reclamation Approach (FRA). Although low‐compaction spoils improve tree survival and growth, erodibility on steep slopes was suspected to increase. This study quantified a combined KC factor (combining the effects of the soil erodibility K factor and cover management C) for low compaction, steep‐sloped (>20°) reclaimed mine lands in the Appalachian region, USA. The combined KC factor was used because standard Unit Plot conditions required to separate these factors, per Revised Universal Soil Loss Equation (RUSLE) experimental protocols, were not followed explicitly. Three active coal mining sites in the Appalachian region of East Tennessee, each containing four replicate field plots, were monitored for rainfall and sediment yields during a 14‐month period beginning June 2009. Average cumulative erosivity for the study sites during the monitoring period was measured as 5248.9 MJ·mm·ha−1·h−1. The KC ranged between 0.001 and 0.05 t·ha·h·ha−1·MJ−1·mm−1, with the highest values occurring immediately following reclamation site construction as rills developed (June – August 2009). The KC for two study sites with about an 18–20 mm spoil D84 were above 0.01 t·ha·h·ha−1·MJ−1·mm−1 during rill development, and below 0.003 t·ha·h·ha−1·MJ−1·mm−1 after August 2009 for the post‐rill development period. The KC values for one site with a 40 mm spoil D84 were never above 0.008 t·ha·h·ha−1·MJ−1·mm−1 and also on average were lower, being more similar to the other two sites after the rill development period. Based on an initial KC factor (Ke) measured during the first few storm events, the average C factor (Ce) was estimated as 0.58 for the rill development period and 0.13 for the post‐rill development period. It appears that larger size fractions of spoils influence KC and Ce factors on low‐compaction steep slopes reclamation sites. Copyright © 2013 John Wiley & Sons, Ltd.